Essentials of Business Analytics, 2nd Edition - Jeffrey D. Camm; James J. Cochran; Michael J. Fry (Cengage Learning, 2016)
ESSENTIALS OF BUSINESS ANALYTICS, 2e can be used by students who have previously taken a course on basic statistical methods as well as students who have not had a prior course in statistics. The expanded material in the second edition of Essentials of Business Analytics also makes it amenable to a two-course sequence in business statistics and analytics. All statistical concepts contained in this textbook are presented from a business analytics perspective using practical business examples. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.